Edukasi Pembuatan Jus Anti GERD pada Ibu-Ibu PKK Desa Kapur Kabupaten Kubu Raya : Education on Making Anti-GERD Juice for PKK Members in Kapur Village Kubu Raya Regency - Wahdaningsih , Sri; Azra, Irfan Yumardi; Anggelina, Silvia; Len, Jelya Wirda; Sari, Zulaika Yogiana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Upper gastrointestinal disorders such as Gastroesophageal Reflux Disease (GERD) are increasingly prevalent in the community, primarily due to irregular eating patterns and unhealthy lifestyles. The adverse effects associated with long-term use of synthetic medications have prompted a shift toward natural remedies. One approach to support this transition is the introduction of a herbal juice made from turmeric, pears, and carrots as a preventive and promotive measure against GERD, particularly targeting homemakers. This program was implemented through a Thematic Community Service (KKN) activity in Kapur Village, Sungai Raya District, West Kalimantan, involving a series of sessions including material presentation, group discussions, hands-on training in herbal juice preparation, and evaluation through pretest and posttest assessments. The activity engaged nine participants from the Family Welfare Empowerment (PKK) group. Evaluation results revealed an improvement in participants' understanding, as reflected in the increase of average scores from 70.22 (pretest) to 80.44 (posttest). The success of this program was supported by local authorities and the community's enthusiastic participation. Overall, the activity proved effective in enhancing public health literacy related to digestive health and in promoting sustainable community empowerment by utilizing local natural resources.